Correlation and pulse techniques for identification of the paths of diffracted and penetrating waves through barriers - CZARNECKI, Stefan; ENGEL, Zbigniew; MIELNICKA, Anna (Archives of Acoustics, 1979)
This paper presents a theoretical analysis and the results of measurements aimed at distinguishing in the total energy transmitted by the barrier, the energy of a wave penetrating the barrier due to its limited insulation and the energy of a wave diffracted at the edge of the barrier.Correlation and pulse techniques have been used in the investigation, to compare the resolution of the two methods for chosen kinds of acoustic signals, i.e. for band noise in the correlation method and for a pulse produced by a spark source in the pulse method. The calculated uncertainty products were the basis for the comparison of resolution agreement between the two methods.